Dolphin Morbillivirus and Toxoplasma gondii coinfection in a Mediterranean fin whale (Balaenoptera physalus) - Mazzariol Sandro; Marcer Federica; Mignone Walter; Serracca Laura; Goria Mariella; Marsili Letizia; Di Guardo Giovanni; Casalone Cristina (BMC Veterinary Research, 2012)
Abstract Background Although Morbillivirus and Toxoplasma gondii have emerged as important pathogens for several cetaceans populations over the last 20 years, they have never been identified together in a Mysticete. In particular, morbilliviral infection has been never described in the Mediterranean fin whale population. Case presentation On January 2011 an adult male of fin whale (Balaenoptera physalus) stranded along the Tyrrhenian coastline of Italy. During necropsy, tissue samples from heart, skeletal muscle, mesenteric lymph nodes, liver, spleen, lung, and kidney were collected and subsequently analyzed for Morbillivirus and Toxoplasma gondii by microscopic and molecular methods. Following the detailed necropsy carried out on this whale, molecular analysis revealed, for the first time, the simultaneous presence of a Dolphin Morbillivirus (DMV) and T. gondii infection coexisting with each other, along with high organochlorine pollutant concentrations, with special reference to DDT. Conclusion This report, besides confirming the possibility for Mysticetes to be infected with DMV, highlights the risk of toxoplasmosis in sea water for mammals, already immunodepressed by concurrent factors as infections and environmental contaminants.